Rapid Detection of Methicillin Resistance in Staphylococcus aureus Isolates by the MRSA-Screen Latex Agglutination Test - van Leeuwen, Willem B. (American Society for Microbiology, 1999)
The slide agglutination test MRSA-Screen (Denka Seiken Co., Niigata, Japan) was compared with the mecA PCR (“gold standard”) for the detection of methicillin resistance in Staphylococcus aureus. The MRSA-Screen test detected the penicillin-binding protein 2a (PBP2a) antigen in 87 of 90 genetically diverse methicillin-resistant S. aureus (MRSA) stock culture strains, leading to a sensitivity of 97%. The three discrepant MRSA strains displayed positive results only after induction of the mecA gene by exposure to methicillin. Both mecA PCR and MRSA-Screen displayed negative results among the methicillin-susceptible S. aureus strains (n = 106), as well as for Micrococcus spp. (n = 10), members of the family Enterobacteriaceae (n = 10), Streptococcus pneumoniae (n = 10), and Enterococcus spp. (n = 10) (specificity = 100%). Producing the same PBP2a antigen, all 10 methicillin-resistant Staphylococcus epidermidis strains score positived in both the latex test and the mecA PCR. Consequently, the MRSA-Screen test should be applied only after identification of the MRSA strain to the species level to rule out coagulase-negative staphylococci. In conclusion, due to excellent specificity and sensitivity the MRSA-Screen latex test has the potential to be successfully used for routine applications in the microbiology laboratory.